Strategic communication and effectiveness analysis of non-profit organizations in the new media era - Liu, Fengjiao; Kasimon, Diyana Nawar (Asian Scholars Network, 2023)
The new media era enables people to obtain information conveniently, and also brings a wider publicity platform to non-profit organizations. So how do non-profit organizations advertise through social networks? The purpose of this paper is to analyze the strategic communication of non-profit organizations based on the new media environment. To this end, a typical case in Malaysia is analyzed: the Green Ribbon Group, a non-profit organization for social utilities. The social movement profile of the nonprofit Green Ribbon Group is examined in the first section. We give the case study evidence in the second section.In this exploratory study, quantitative methods were chosen to gather public perceptions of the effectiveness of the communication strategies used by the "Green Ribbon Group" in its social campaigns from 50 respondents. This was done in light of the connections between strategic communication and the non-profit sector. This case study was specifically intended to show the kinds of communication tactics that a non-profit organisation could create. Reveals how nonprofits create and maintain a wide range of relationships between the organization and stakeholders through strategic communications.